2008
DOI: 10.1016/j.steroids.2008.05.004
|View full text |Cite|
|
Sign up to set email alerts
|

Validation of a testosterone and dihydrotestosterone liquid chromatography tandem mass spectrometry assay: Interference and comparison with established methods

Abstract: Testosterone (T) and its metabolite dihydrotestosterone (DHT) are androgens with different biologic profiles. T and DHT measurements are required for assessment of patients with ambiguous genitalia, hirsutism, during 5 alpha reductase treatment of prostate disorders, and new androgen formulations. Our laboratory has developed and validated a method to simultaneously measure serum T and DHT with liquid chromatography tandem mass spectrometry (LC-MS/MS) for use in a clinical chemistry laboratory. Analysis of ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
1
3

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(46 citation statements)
references
References 39 publications
3
39
1
3
Order By: Relevance
“…At present, RIA and LC-MS/MS are commonly used for measuring TT, but it is not clear whether the discordance between the 2 methods could affect the classification of hypogonadism. In this study, we showed that the correlation between TT concentrations determined by RIA and LC-MS/MS was reasonably high, consistent with previous observations (5)(6)(7)(8). At the individual level, this correlation translated into some inconsistency in the classification of male hypogonadism between the 2 methods of measurement, regardless of the serum TT thresholds used.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…At present, RIA and LC-MS/MS are commonly used for measuring TT, but it is not clear whether the discordance between the 2 methods could affect the classification of hypogonadism. In this study, we showed that the correlation between TT concentrations determined by RIA and LC-MS/MS was reasonably high, consistent with previous observations (5)(6)(7)(8). At the individual level, this correlation translated into some inconsistency in the classification of male hypogonadism between the 2 methods of measurement, regardless of the serum TT thresholds used.…”
Section: Discussionsupporting
confidence: 89%
“…The inconsistency between that study and ours could be a result of differences in the population studied, RIA methods used, or method of data analysis. The participants in the study of Wang et al (8 ) were much younger and less likely to have a low TT concentration than our participants. Wang et al (8 ) recruited 122 men, ages 18 -68 years; meanwhile, all 602 elderly men in our study were age Ն60 years old, with a mean age of 73 years.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…The next steps in the sample preparation procedure were adapted from two published methods for total testosterone (26,30 ). In brief, testosterone was released from binding proteins with 600 L ammonium acetate (0.5 mol/L, pH 5.5) and equilibrated at room temperature (22°C) for 2 h. Liquid/liquid extraction (LLE) was performed 2 times with 2.5 mL ethyl acetate:hexane solution (3:2, vol:vol) to extract the analytes.…”
Section: Sample Preparationmentioning
confidence: 99%